Uncertainty about paternity: a study on deliberate ignorance - Gigerenzer, Gerd; Garcia-Retamero, Rocio (Frontiers in Psychology, 2024)
Deliberate ignorance is the willful choice not to know the answer to a question of personal relevance. The question of whether a man is the biological father of his child is a sensitive issue in many cultures and can lead to litigation, divorce, and disinheritance. Thanks to DNA tests, men are easily able to resolve the uncertainty. Psychological theories that picture humans as informavores who are averse to ambiguity suggest men would do a DNA test, as does evolutionary theory, which considers investing in raising a rival's offspring a mistake. We conducted two representative studies using computerbased face-to-face interviews in Germany (n = 969) and Spain (n = 1002) to investigate whether men actually want to know and how women would react to this desire. As a base line, Germans (Spanish) estimated that 10% (20%) of fathers mistakenly believe that they are the biological father of their child. Nevertheless, in both countries, only 4% of fathers reported that they had performed a DNA paternity test, while 96% said they had not. In contrast, among men without children, 38% (33%) of Germans (Spanish) stated they would do a DNA test if they had children, mostly without telling their partners. Spanish women with children would more often disapprove of a paternity test or threaten their husbands with divorce (25%) than would German women (13%). We find that a simple test of risk aversion, measured also by the purchase of nonmandatory insurances, is correlated with not wanting to know.